The Effect of Consumer Experience and Food Quality on Customer Satisfaction of Culinary MSMEs in Jakarta moderated by Entrepreneurial Character - Kustiadi Basuki; Detiya Marliyana (Budapest International Research and Critics University, 2022)
The purpose of this study was to examine and determine the effect of customer experience and food quality on customer satisfaction of culinary SMEs in Jakarta moderated by entrepreneurial character. The sampling technique used was accidental sampling and the samples used in this study were 210 MSME customers in Jakarta. The data collection technique uses a questionnaire instrument and then the data that has been collected is processed by data analysis methods in the form of SEM-PLS and Smart PLS Version 03 software. The results of this study indicate that customer experience and food quality have a positive and significant effect on customer satisfaction, while entrepreneurial character has an effect on positive on customer satisfaction. Based on the moderating variable, the entrepreneurial character has not been able to strengthen the influence of customer experience on customer satisfaction, while the entrepreneurial character is able to strengthen the influence of food quality on customer satisfaction.